Caste- and age-specific venom composition of biogenic amines and the influence of diet in honey bees - Motoharu Hamano; Kazuya Niki; Keiki Imamura; Ken Sasaki (PLoS ONE, 2025)
The chemical composition of the venom in social Hymenoptera differs between castes and ages. Biogenic amines are contained in the venom of honey bees and may be physiologically effective to vertebrate predators and insects. This study quantified the concentrations of biogenic amines in venom and compared them between different castes and ages of honey bees. The concentrations of dopamine and N -acetyldopamine in venom were significantly higher in virgin queens than workers of the same age. The concentrations of dopamine, norepinephrine, tyramine and serotonin increased with age in virgin queens and workers. There was a significant positive correlation between venom dopamine concentrations and ovarian development in queenless workers, suggesting that the concentration of dopamine in the venom transformed from normal workers to reproductive females as that in virgin queens. We also tested the possibility of dietary effects on the concentration of dopamine in venom. Workers fed tyrosine or royal jelly showed significantly higher concentrations of dopamine precursors, tyrosine, 3,4-dihydroxyphenylalanine (DOPA) and dopamine in the hemolymph, as well as higher concentrations of dopamine in venom than in controlled workers. These results suggest that compositions of biogenic amines in venom are influenced by nutrition and change based on their social roles in honey bee society.